s+6=4

Simple and best practice solution for s+6=4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for s+6=4 equation:


Simplifying
s + 6 = 4

Reorder the terms:
6 + s = 4

Solving
6 + s = 4

Solving for variable 's'.

Move all terms containing s to the left, all other terms to the right.

Add '-6' to each side of the equation.
6 + -6 + s = 4 + -6

Combine like terms: 6 + -6 = 0
0 + s = 4 + -6
s = 4 + -6

Combine like terms: 4 + -6 = -2
s = -2

Simplifying
s = -2

See similar equations:

| -6=6x-6+x | | -(y-3)=2y+6 | | 4.50+0.05=0.20x-4.50 | | 4=-8.0n | | x+(26+x)=64 | | 5w^2+12w^2= | | 8(y-1)=3y+17 | | -5k-2k=14 | | -4-9/3=-7 | | -7(n+3)=-34+6n | | 64x^2-192x=0 | | 4.7=30 | | .4*-.03= | | 7x+22=11x+68 | | V-39=-17 | | 3=k+4+5 | | 21x+3=12x+6 | | -(1-7x)=4x-13 | | 2x^2-12x-27=0 | | 5=5-4s-7s | | .4x-.03= | | 3x+x+40=180 | | x-20+2-(-7)=9 | | 3b-5+6b=-5 | | 1/6X-5=-11 | | 11-(8-8n)=8 | | (-16)-(-t)=(-45) | | 4(7y-3)= | | 3(2x+1)-5=10 | | 100n+10n=0n+15n | | -1(-m+n+1)= | | 1/5+1/4x=1/3x+5/6 |

Equations solver categories